Untraditional couples in a neo-traditional setting. Which women perform as much paid work as their partner? - Ragni Hege Kitterød; Marit Rønsen (Statistics Norway, Research Department, 2010)
An equal division of paid and unpaid work is a central political ambition in Norway. Yet, couples' division of paid work has been less studied than their division of unpaid work. This paper shows that women seldom work more than their partner, but equal sharing is now increasing. Still, about half of all women spend less time than their partner on paid labour. When the woman works most, the partner often has health problems, is unemployed or retired. Women with an untraditional arrangement are often well-educated, have no young children, are self-employed, leaders, or have a partner in the public sector. Nurses often work less than their partners, as do women who have young children, health restrictions or a partner who works in the private sector, is self-employed or a leader.
Keywords: J22; J24; J45; 330; Dual-earner couples; female labour supply; gender equality.